Eine zweite Art der Gattung Cyphon paykull aus der Wallacea. 54. Beitrag zur Kenntnis der Helodidae (Coleoptera, Helodidae). - Klausnitzer, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 1981)
A new species of the genus Cyphon Paykull,1799, from the island of Mangole (Sula Islands), Cyphon mangolensis spec. nov. is described. Its nearest relations seem to be Cyphon setulosus Klausnitzer, 1973, and Cyphon postcornutus Klausnitzer, 1973, from the Philippines, Cyphon scabridus Klausnitzer, 1980 (New Guinea), Cyphon pilumnus Klausnitzer, 1980 (Sumatra) and Cyphon carus Klausnitzer, 1980 (Malaysia).Nomenclatural Actsmangolensis Klausnitzer, 1981 (Cyphon), spec. n.